2022
DOI: 10.1111/jdi.13831
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of dual agonist of glucagon and glucagon‐like peptide‐1 receptors to achieve functional restoration of first‐ and second‐phase insulin secretion

Abstract: The role of glucagon and GLP‐1 receptors in first and second phase insulin secretion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A recent review paper described glucagon's important role in glucose homeostasis with respect to the GLP‐1 receptor, 20 and a mechanistic study of cotadutide suggested its glucose‐lowering effects are mediated by enhanced insulin secretion together with delayed gastric emptying 12 . In our study, cotadutide reduced the time spent in hyperglycaemia as measured by CGM and reduced 7‐day mean glucose levels from the dose of 50 μg, with a maximal effect reached at the 200‐μg dose that was maintained up to the 600‐μg dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review paper described glucagon's important role in glucose homeostasis with respect to the GLP‐1 receptor, 20 and a mechanistic study of cotadutide suggested its glucose‐lowering effects are mediated by enhanced insulin secretion together with delayed gastric emptying 12 . In our study, cotadutide reduced the time spent in hyperglycaemia as measured by CGM and reduced 7‐day mean glucose levels from the dose of 50 μg, with a maximal effect reached at the 200‐μg dose that was maintained up to the 600‐μg dose.…”
Section: Discussionmentioning
confidence: 99%
“…11,[16][17][18] A reduction in systolic BP and an increase in pulse rate were observed in this study, consistent with the results of a phase IIb study of cotadutide 13 and those of a study of semaglutide (a GLP-1 receptor mono-agonist). 19 A recent review paper described glucagon's important role in glucose homeostasis with respect to the GLP-1 receptor, 20 and a mechanistic study of cotadutide suggested its glucose-lowering effects are mediated by enhanced insulin secretion together with delayed gastric emptying. 12 In our study, cotadutide reduced the time spent in hyperglycaemia as measured by CGM and reduced 7-day mean glucose levels from the dose of 50 μg, with a maximal effect reached at the 200-μg dose that was maintained up to the 600-μg dose.…”
Section: Immunogenicitymentioning
confidence: 99%